2018
DOI: 10.1093/femspd/fty032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of temperature on protein abundance in Demodex-associated Bacillus oleronius

Abstract: A potential role for bacteria in the induction of rosacea has been suggested. The aim of this work was to characterise the effect of temperature on the production of immunostimulatory proteins by Bacillus oleronius-a bacterium to which rosacea patients show sera reactivity and which was originally isolated from a Demodex mite from a rosacea patient. The affected skin of rosacea patients is at a higher temperature than unaffected skin, and it was postulated that this might alter the protein expression pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Remarkably, B. oleronius presented antigens that significantly stimulated the proliferation of peripheral blood mononuclear cells to a greater degree in rosacea patients than in controls (Lacey et al, 2007). Further studies have confirmed the immunoreactivity of rosacea patients to 62-and 83-kDa proteins of B. oleronius (O'Reilly et al, 2012;Jarmuda et al, 2014) showed that typical increased skin temperature of rosacea patients modified growth and protein pattern of B. oleronius leading to a greater production of immunoreactive proteins (Maher et al, 2018). Therefore, there is evidence that bacteria provided by Demodex mites can aggravate the established inflammatory response in rosacea.…”
Section: Skin Microbiota and Pathophysiology Of Rosaceamentioning
confidence: 85%
See 1 more Smart Citation
“…Remarkably, B. oleronius presented antigens that significantly stimulated the proliferation of peripheral blood mononuclear cells to a greater degree in rosacea patients than in controls (Lacey et al, 2007). Further studies have confirmed the immunoreactivity of rosacea patients to 62-and 83-kDa proteins of B. oleronius (O'Reilly et al, 2012;Jarmuda et al, 2014) showed that typical increased skin temperature of rosacea patients modified growth and protein pattern of B. oleronius leading to a greater production of immunoreactive proteins (Maher et al, 2018). Therefore, there is evidence that bacteria provided by Demodex mites can aggravate the established inflammatory response in rosacea.…”
Section: Skin Microbiota and Pathophysiology Of Rosaceamentioning
confidence: 85%
“…Moreover, McMahon et al demonstrated how B. oleronius proteins can induce neutrophil recruitment through activation of the inositol trisphosphate (IP3) pathway with production of proinflammatory cytokines ( McMahon et al, 2016 ). Maher et al showed that typical increased skin temperature of rosacea patients modified growth and protein pattern of B. oleronius leading to a greater production of immunoreactive proteins ( Maher et al, 2018 ). Therefore, there is evidence that bacteria provided by Demodex mites can aggravate the established inflammatory response in rosacea.…”
Section: Pathophysiology Of Rosaceamentioning
confidence: 99%
“…Exposure of neutrophils to proteins from B. oleronius resulted in degranulation and the production of inflammatory cytokines [22,23]. The increased temperature of the inflamed skin of rosacea patients alters the growth and increases the 62-kDa protein production of B. oleronius [24] and thus, continuously re-stimulates the inflammatory response.…”
Section: The Role Of Microbes In the Pathogenesis Of Rosaceamentioning
confidence: 99%
“…LFQ proteomics of T. aggressivum and A. bisporus treated with B. velezensis supernatant Proteins were extracted according to Maher et al (2018) from A. bisporus mycelium which was grown for 8-days and then supplemented with B. velezensis supernatant (n = 3) for an additional 2-days. Proteins were also extracted from T. aggressivum mycelium which was grown for 24 h and then supplemented with B. velezensis supernatant (n = 3) for an additional 24 h. The Bradford method was used to quantify proteins for acetone precipitation overnight.…”
Section: Effect Of B Velezensis Supernatant On a Bisporus Growthmentioning
confidence: 99%